Weight bias, health consciousness and behavioral actions (activities). (December 2016) - Wood, Matthew; Shukla, Paurav
Abstract : Objective: This study examines the influence of weight bias and health consciousness on eating and dietary behavior; it also investigates the role of normative influences. Design and methods: A sample of adults living in South-East England (N = 498) completed anonymous questionnaires about their diet, attitudes and beliefs towards obese people, health consciousness and normative influences. The survey included validated measures of anti-fat attitudes, and beliefs about obese people. Results: The findings demonstrate anti-fat attitudes are positively related to self-perceived dietary behavior. Surprisingly, self-perceived dietary behavior is negatively related to health consciousness and activities designed to enable healthy eating, for example meal planning. Significant differences exist between people with, or without, obese family members. Conclusions: Attempts to improve eating behavior by raising health consciousness and offering related support activities may fail; promoting health eating may also contribute to weight bias in society. However, interventions which focus on the negative impact of obesity itself may have a positive effect. Highlights: This study examines the influence of weight bias and health consciousness on eating behavior. Anti-fat attitudes are positively related to self-perceived dietary behavior. Self-perceived dietary behavior is negatively related to health consciousness. Eating behavior is negatively related to support activities such as meal planning. Significant differences exist between people with, or without, obese family members.